(untitled) (International Journal of Engineering and Computer Science, 2018)
A Computing system is one,where an input data compared with a stored data to locate the matching entry.For example translation look aside buffer and Cache tag array lookup matching. In this paper, we propose new architecture in order to reduce complexity and latency for matching the data protected with an error-correcting code(ECC). It is based on the codeword of an ECC generated by encoding is usually represented in a systematic form and it consists the raw data and the parity information. The proposed architecture parallelizes the comparison of the data and that of the parity information.To reduce the latency and complexity, we propose a new butterfly-formed weight accumulator(BWA) for The efficient computation of the Hamming distance.The proposed architecture checks whether the incoming data matches with the stored data.